(untitled) (PJDOL, 2023)
Web, an internet platform, is accessible through technology devices for given information, but its role has been shifted towards the instructional delivery system. However, its usefulness, utilisation, and importance to learning is yet to be explored. Therefore, the present study investigated the effectiveness of web-based instruction package on the learners' academics performances in visual arts in Nigerian Senior Secondary School. Pre and post-test group were adopted for 60 Senior Secondary Schools, of class two (SSS II) learners from three co-educational and recognised non-governmental schools in Ogbomoso, Oyo State. Nigeria. Research questions and null hypotheses are formulated for the study at 0.05 level of significance. Visual Arts Web-Based Performance Test (VAWPT) consisted of 50 validated items, from NECO and WASSCE visual arts past examination. The data were analyzed with ANCOVA, ttest, and ANOVA for three hypotheses. The study revealed that learners taught under WBI Package performed well and there was no significant difference between the mean scores of both male and female visual arts learners exposed to Web-Based Instruction (WBI) Package.